THE CONCEPT OF MARRIAGE FROM THE HASBI ASH-SHIDDIEQY PERSPECTIVE : An Approach Maqasidi On Verses of Polygamy and Inter-religious Marriage Tafsir An-Nuur - Ibrahim, Muhammad Syahrial Razali (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2023)
Abstract: The aim of this article is to elucidate modernist Islam position on the discourse of poligamy and interfaith marriage based on the work of Hasbi ash-Shiddieqy’s Tafsīr An-Nuur.  In response to the issues, he argues that the objectives of Shari`a are pivotal. The law on poligamy and interfaith marriage are both contextualised by the realisation of Shari'a objectives. Here, he views that both of poligamy and interfaith-marriage are forbidden for the first is incapable of actualisation domestic justice, while  the second is against Shari'a maqashid; hifdh al-dīn/ the protection of sound religious practices. By relying on descriptive analytic of Hasbi’s work on the tafsir, it is found that he views the domestic justice encrypted in al-Nisâ’ 3 and 129 is both physical needs and psychological actualisation, which are to some extent impossible to be achieved by poligamy. He furthers accordingly that interfaith marriage is prone to  deteriorate   Islamic principles and practices.Keywords: interfaith marriage, poligamy, Hasbi Al-Shidiqy, and Modernist Islam